An electrochemical and computational study for discrimination of d- and l-cystine by reduced graphene oxide/β-cyclodextrin. Issue 1 (10th November 2014) - Zor, Erhan; Bingol, Haluk; Ramanaviciene, Almira; Ramanavicius, Arunas; Ersoz, Mustafa
Abstract : This study indicates the applicability of two different techniques (electrochemical and computational study) for the discrimination of cystine enantiomers (d - andl -cystine) by reduced graphene oxide/β-cyclodextrin (rGO/β-CD) hybrid material. Abstract : Here, we report a novel enantioselective electrochemical biosensor for the discrimination of cystine enantiomers (d - andl -cystine) using a chiral interface for the specific recognition ofd - andl -cystine. The biosensor is based on reduced graphene oxide modified by β-cyclodextrin (rGO/β-CD) at the GCE surface. During the preparation of rGO/β-CD/GCE, the modified electrode surfaces were characterized by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and scanning electron microscopy (SEM). The electrochemical behaviours of thed - andl -cystine were investigated using the rGO/β-CD/GCE by CV and compared to bare GCE. A clear separation between the oxidation peak potentials ofd - andl -cystine was observed at 1.32 and 1.42 V, respectively. The electrochemical discrimination performance of the fabricated chiral sensor was also examined by differential pulse voltammetry (DPV) in a mixed solution ofd - andl -cystine. In addition, the DPV technique was used for the determination ofd - andl -cystine at low concentration values in the range of 1.0–10.0 μM. To investigate the amperometric response of rGO/β-CD/GCE towardsd - andl -cystine, the chronoamperometry technique was used in the concentration range of 10.0–100.0 μM. The interactions of the enantiomers with rGO/β-CD were modelled by molecular docking using AutoDock Vina, and the interaction energies were predicted to be −4.8 and −5.3 kcal mol −1 ford - andl -cystine, respectively. The corresponding values of binding constants were calculated to be 3.32 × 10 3 and 7.71 × 10 3 M −1, respectively. The experimental and molecular docking results indicate that the rGO/β-CD/GCE has a different affinity for each enantiomer.